The concept of "Neolithic package" - Çilingiroglu, Çiler (Documenta Praehistorica, 2005)
In this paper, one of the most frequently used terms in Neolithic studies, e.g. the so-called "Neolithic package", will be discussed. Apart from providing a brief historical background of the term and how it was used since the 80's, the text will concentrate on a plausible definition and the possible contents of the package which can be observed as a common set of objects in Southwest Asia, Anatolia and Southeast Europe. It will be argued that the use of this concept has both advantages and disadvantages. Although the term provides a macro level look to the large geography mentioned above, that was obviously closely interconnected in the course of 7th and 6th millenia BC, the term should be implemented cautiously at regions where the elements of the package do not seem to be fully integrated into the life of the groups.
Keywords: arheološke najdbe; neolitik; strokovna terminologija